UREILITE METEORITES: EQUILIBRATION TEMPERATURES AND SMELTING REACTIONS - Sinha S.K.; Sack R.O.; Lipschutz M.E. (My University, 1997)
We report microprobe analyses for eight ureilite samples (ALH A78019, ALH 82106, ALH 82130, ALH 84136, LEW 85328, LEW 85440, MET A78008, and RKP A80239) and calibrate smelting reactions characteristic of ureilites using the experimental data of Walker and Grove (1993) and the thermochemical models of Sack and Ghiorso (1989, 1994a-c). The quenching temperatures for pyroxenes (1200-1070°C) that we derive using the approach of Sack and Ghiorso (1994b) and our chemical data for augite-orthopyroxene and pigeonite-orthopyroxene assemblages are related to the molar MgO/(MgO + FeO) ratio (mg#) of olivines and to the Δ 17O of ureilites determined by Clayton and Mayeda (1988). We infer that these ureilites are from three subgroups which are from at least three parent regions, perhaps disconnected on a single parent body or from different parent bodies. Samples from the subgroup with the highest olivine mg#s (subgroup III) exhibit the most extensive smelting of silicates through reactions with carbonaceous materials, record equilibration temperatures of 1200 +/- 15°C, and appear to be derived from near-surface regions of their parent asteroids. Samples from the subgroup with the lowest olivine mg#s (subgroup I) have undergone the most limited smelting of silicates and record equilibration temperatures in the range 1100-1070°C. The formation depth of this subgroup, hence the minimum radius of the asteroid, was at least 50 km. Samples from the subgroup with intermediate olivine mg#s and Δ 17O values (subgroup II) record equilibration temperatures of 1230 +/- 15°C, do not appear to represent mixtures of the other subgroups, and may require an even larger parent body(ies).